(untitled) (SAARC Journal of Agriculture, 2016)
The five cotton cultivars viz., CB1, CB3, CB5, CB8, and C12 were evaluated under field conditions to compare their resistance levels against the aphid species Aphis gossypii (Hemiptera: Aphididae) and the jassid species Amrasca devastans (Hemiptera: Cicadellidae). The effects of plant characteristics that could explain some of the varietal resistance levels were tested by measuring infestation levels, biochemical content, leaf trichome density, agronomic traits, yield, and quality of seed and fiber. In comparison with other varieties, CB1 and CB3 showed the least leaf and boll infestation, and possessed higher numbers of trichomes. CB12 had the lowest number of trichomes and exhibited the highest percentages of leaf and boll infestation. Biochemical analyses indicated that the highest percentage of starch occurred in CB8, and that of protein in CB5. Both starch and protein content were lowest in CB12. Aphid and jassid infestation reduced the starch and protein content of all cultivars. CB3 was the best performing variety in terms of size and weight of bolls; ginning out-turn (GOT); number of branches, leaves, and bolls per plant; and number of locules per boll. Seed cotton yields and lint indices were highest in CB1 and CB3 and lowest in CB12. CB12 was also the worst performing variety in terms of plant height, micronaire value, percentage of GOT and germination, number of leaves and bolls per plant, and boll length, width and weight. The findings of this study clearly demonstrate that, among the cultivars evaluated, CB12 is the most susceptible to aphid and jassid infestation. SAARC J. Agri., 14(1): 11-23 (2016)